German Jews : a dual identity - Mendes-Flohr, Paul R. (Yale University Press, 1999)
In this book the author explores through the prism of Rosenweig's image of how German Jews have understood and contended with their two-fold spiritual patrimony. He deepens the discussion to consider also how the German-Jewish experience bears upon the general random experience of living with multiple cultural identities.